Effect of Suryanamaskar Practice on Cardio-respiratory Fitness Parameters: A Pilot Study - Pratima M. Bhutkar (Al Ameen Medical College, 2008)
: In recent times, medical fraternity is attracted towards yoga . Suryanamaskar is a part of yogic practices and is believed to be an all-round exercise. The present study tested efficacy of regular practice of 'suryanamaskar' in improving the cardio-respiratory fitness. The present study was conducted on 78 subjects, (48 males and 30 females). It was observed that 6 months of suryanamaskar practice decreases resting pulse rate and blood pressure. At the same time it increases cardio-respiratory efficiency and respiratory capacity as evaluated by bicycle ergometry and various lung functions tests, in both male and female subjects. From this study we conclude that suryanamaskar practice can be advocated to improve cardio-respiratory efficiency for patients as well as healthy individuals.